Draft Five Year Plan 1978-83 Social Education and Community Listening Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
Besides this, under the directive of the central Govt. a provision of Rs 68.64 lakh has been made for the maintenance of office vehicles T.A. etc. for the additional staff to be provided for the directorate and district level by the Central Govt.
Government of Madhya Pradesh, Planning, Economics and Statistics Department